Tanggapan Alkitab dan Gereja Terhadap Faktor Pemicu Terjadinya Perceraian - Sele, Ricu; Zacheus, Soelistiyo Daniel (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2021)
The divorce rate in Indonesia is increasingly showing a significant upward trend. Therefore, this study aims to describe the factors of divorce, the response of Lakit and the church to the divorce. Divorce doesn't just happen. Divorce is triggered by various factors. These factors are used as justification for conducting a divorce. Those reasons are used as the basis for suing and carrying out a divorce. The Bible is against divorce. God hates divorce. God never designed a marriage for divorce. Biblical marriage is marriage for life. Marriage must be built on a strong foundation, namely love. Like the bond of love between Christ and His church, so is the bond of husband and wife in a marriage. The church is in line with the Bible / Word of God, does not tolerate divorce. The church must strive to prevent its people from divorcing. Because divorce does not solve problems, but in Christ and His love all problems that arise in marriage can be resolved. He is in Christ and in His love there must be a way out. The method used by researchers in this writing is descriptive qualitative by using literature sources that support the writing of this article. Hopefully the results of this research can be a reference for pastors and churches and people to solve every problem in marriage wisely so that it doesn't end in divorce. Angka perceraian di Indonesia semakin menunjuk tren peningkatan yang signifikan. Karena itu penelitian ini bertujuan untuk memaparkan faktor-faktor perceraian, tanggapan Alkitab dan gereja terhadap perceraian tersebut. Perceraian dipicu oleh berbagai faktor. Alasan-alasan itulah yang dijadikan sebagai dasar untuk menuntut dan melakukan perceraian. Alkitab menentang perceraian. Tuhan tidak pernah merancang sebuah pernikahan untuk perceraian. Pernikahan Alkitabiah adalah pernikahan seumur hidup. Pernikahan harus dibangun dasar yang kuat yaitu kasih. Seperti ikatan kasih antara Kristus dan jemaatNya. Gerejapun sejalan dengan Alkitab/Firman Allah, tidak mentolerir adanya perceraian. Gereja harus berjuang untuk menghindarkan umatnya dari perceraian. Sebab perceraian tidak menyelesaikan masalah, tetapi di dalam Kristus dan kasihNya semua persoalan yang muncul dalam pernikahan bisa diselesaikan. Adapun metode yang dipergunakan peneliti dalam penulisan ini adalah deskriptif kualitatif dengan menggunakan sumber-sumber literatur yang mendukung penulisan artikel ini. Kiranya hasil penelitian ini, dapat menjadi acuan bagi Pendeta dan gereja serta umat untuk menyelesaikan setiap masalah dalam pernikahan secara bijak sehingga tidak berakhir dengan perceraian.